Testing excess returns from passive options investment strategies - José P. Dapena; Julian R. Siri (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2017)
When analyzing options returns, most papers tend to focus on the expected and realized return from strategies where the investors are long on those financial instruments. We conduct a test searching for excess returns on passive options investment strategies resorting to a four factor model, evaluating the case of an investor who launches options and evaluates returns to the light of capital invested in the form of margins requirement. The main point of our research work is to continue the line of research where we evaluate options returns using the metrics with respect to margin requirements. We find that there are excess returns not explained by the four factor model, which in turn may indicate the strategy generates extra returns, or that the investor going short on options provides insurance to events not captured by the traditional models.
Keywords: C1; C3; N2; G11; 330; four factor model; asset pricing; realized returns; option pricing